2007
DOI: 10.1111/j.1365-2672.2006.03257.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of Photobacterium damselae ssp. piscicida from cultured amberjacks (Seriola spp.) in Japan by pulsed-field gel electrophoresis and plasmid profiles

Abstract: Aims: This study deals with a pulsed-field gel electrophoresis (PFGE) for discriminating between the genetic variants of Photobacterium damselae ssp. piscicida, and characterizing of Japanese field isolates by PFGE together with plasmid profiles and antimicrobial resistances. Methods and Results: A total of 74 field isolates from cultured Japanese amberjacks were used for PFGE. SmaI and NotI enabled to clearly differentiate strains and we obtained 24 of combined PFGE profiles which were distinct from those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
6
2
Order By: Relevance
“…In addition, the genetic heterogeneity of this pathogen was previously described when 18 and 11 digesting patterns were obtained using the same restriction enzymes from 74 Japanese field isolates of Phdp (Kijima‐Tanaka et al, 2007). Interestingly, the PFGE results using SmaI as the restriction enzyme in this study and the study by Kijima‐Tanaka et al (2007) are in contrast to those reported by Lucangeli et al (2000), where all 20 Italian field strains showed an identical profile. This suggests that different observations are dependent on the number of isolates, host diversity or the current situation of a specific geographical area.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the genetic heterogeneity of this pathogen was previously described when 18 and 11 digesting patterns were obtained using the same restriction enzymes from 74 Japanese field isolates of Phdp (Kijima‐Tanaka et al, 2007). Interestingly, the PFGE results using SmaI as the restriction enzyme in this study and the study by Kijima‐Tanaka et al (2007) are in contrast to those reported by Lucangeli et al (2000), where all 20 Italian field strains showed an identical profile. This suggests that different observations are dependent on the number of isolates, host diversity or the current situation of a specific geographical area.…”
Section: Discussionmentioning
confidence: 97%
“…To determine the genetic variants of Phdp isolates in different years (2016–2018), the PFGE method was performed, as described previously (Kijima‐Tanaka et al, 2007) with modification. Briefly, Phdp isolates were cultured on TSN agar and harvested, and the cell suspension was adjusted to an OD 600 of 2 in cell suspension buffer (100 mM Tris–HCl, 100 mM EDTA, pH = 8.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a DNA-containing agar plug of each sample was prepared by the previously reported method (Kijima-Tanaka et al, 2007) with the following modifications. Culture fluid containing about 10 8 cells was put into a 15-ml centrifuge tube and centrifuged at 9,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…piscicida isolated from amberjacks ( Seriola spp.) in Japan found that all strains had several plasmids (Kijima‐Tanaka et al , 2007). Even though this locally emerging population showed only subtle genomic differences among strains, the distribution of plasmids was heterogeneous.…”
Section: Heterogeneous Distribution Of Plasmids In Bacterial Populationsmentioning
confidence: 99%